Biochar considerably increases the easily available water and nutrient content in low-organic soils amended with compost and manure. (April 2022) - Seyedsadr, Samar; Šípek, Václav; Jačka, Lukáš; Sněhota, Michal; Beesley, Luke; Pohořelý, Michael; Kovář, Martin; Trakal, Lukáš
Abstract: The soil hydraulic properties of two low-organic soils (Fluvisol; Regosol) were investigated following their amendment with biochar alone or in combination with manure, compost and co-composted biochar. Self-irrigating boxes containing the soil and amendment combinations were purposed with a battery of soil moisture sensors as well as soil porewater sampling devices. Static sampling determined bulk density, porosity and derived soil water retention curves. The aim of this study was to identify the most advantageous amendment combinations to enhance soil water retention whilst simultaneously avoiding excessive nutrient leaching arising, primarily, from manure application. Biochar significantly decreased bulk density and increased total porosity when compared to compost in the Fluvisol, whereas manure affected the greatest changes in the Regosol. All of the tested amendments adjusted the shape or extent of the soil water retention curves, but biochar addition resulted in the greatest increase (⁓50%) in easily available water content (for plants) in both soils, when compared to the control. Saturated hydraulic conductivity was, however, not changed by any of the amendments which reflects a lack of influence on infiltration. An enhancement in nutrient retention occurred in some of the soil amendment configurations, such as for co-composted biochar at 2% dosage and 5% manure-biochar mixture, as revealed by porewater analysis. In summary, the application of biochar with and without additional compost and manure can enhance soil water retention in low-organic soils whilst maintaining or enhancing nutrient retention. Such finding supports the application of mixed organic amendments to low-organic (and therefore drought-prone) arable soils. Graphical abstract: Image 1 Highlights: Biochar, manure and their combination were tested for soil drought relief in a Regosol and Fluvisol. Soil bulk density and porosity were most considerably impacted by manure. Nutrient leaching from manure was significantly mitigated by biochar presence. Biochar changed the profile but not magnitude of the soil water retention curve. Plant available water content was greatest after biochar amendment.